CIVILIZAÇÃO NACIONAL A PARTIR DE FORA: política e cultura em La Revista Literaria no Uruguai (1865) - DIANA, ELVIS DE ALMEIDA (Outros Tempos: Pesquisa em Foco - História, 2019)
We propose to analyze the political-cultural performance of the periodical La Revista Literaria, founded by several intellectuals in 1865, seeking to understand it both as a space for intellectual and citizen formation, based on the indications of Hilda Sabato (2008). We also aimed to understand how his publications proposed an identity for Uruguay of that period, aiming at the "civilization" of national character for the population of that country. The journal's work focused on criticism of the Uruguayan Catholic Church and the Spanish monarchist past that still seemed to be present amid the internal attempts to consolidate the post-independence National State. However, this project took place by looking "outwardly" through external references, thus constituting a form of perception of a temporal "movement" - in Reinhart Koselleck's (2006) words -towards "modernity" political-cultural Uruguayan national. Keywords: Uruguay. Civilization. La Revista Literaria.